The international consensus classification of eosinophilic disorders and systemic mastocytosis - Wang, Sa A.; Orazi, Attilio; Gotlib, Jason; Reiter, Andreas; Tzankov, Alexandar; Hasserjian, Robert P.; Arber, Daniel A.; Tefferi, Ayalew (American journal of hematology, 2023)
Based on new data and increased understanding of disease molecular genetics, the international consensus classification (ICC) has made several changes in the diagnosis and classification of eosinophilic disorders and systemic mastocytosis. Myeloid/lymphoid neoplasms with eosinophilia (M/LN-eo) and gene rearrangements have been renamed as M/LN-eo with tyrosine kinase gene fusions (M/LN-eo-TK). The category has been expanded to include ETV6::ABL1 and FLT3 fusions, and to accept PCM1::JAK2 and its genetic variants as formal members. The overlaps and differences between M/LN-eo-TK and BCR::ABL1-like B-lymphoblastic leukemia (ALL)/de novo T-ALL sharing the same genetic lesions are addressed. Besides genetics, ICC for the first time has introduced bone marrow morphologic criteria in distinguishing idiopathic hypereosinophilia/hypereosinophilic syndrome from chronic eosinophilic leukemia, not otherwise specified. The major diagnostic criteria for systemic mastocytosis (SM) in the ICC remain largely based on morphology, but several minor modifications/refinements have been made in criteria related to diagnosis, subclassification, and assessment of disease burden (B- and C-findings). This review is to focus on the ICC updates related to these disease entities, illustrated through changes related to morphology, molecular genetics, clinical features, prognosis, and treatment. Two practical algorithms are provided in navigating through the diagnosis and classification systems of hypereosinophilia and SM.